2009
DOI: 10.1177/0040517508097521
|View full text |Cite
|
Sign up to set email alerts
|

Surface Trimer Removal of Polyester Fibers by Ozone Treatment

Abstract: The oxidative ozone treatment of poly (ethylene terephthalate) fibers after dyeing was recently proposed as a novel afterclearing method. High fastness properties, energy and time savings, and environmental benefits were reported by the ozone treatment compared to the conventional reduction clearing. This study investigated the efficiency of the ozone treatment afterclearing process on the surface trimer removal of poly(ethylene terephthalate) fibers. Results indicated similar cyclic trimer [(GT)3] removal rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Successful and advantageous ozone treatment trials for the after clearing of disperse dyed polyester have been reported in the literature. These studies report the use of ozone at room temperature for shorter treatment times compared with conventional reduction clearing, with satisfactory colour difference values and wash fastness results for the ozone treatments .The potential benefits of ozone utilisation for the clearing of disperse dyed PET in terms of lower environmental pollution and water, energy, and time savings have been reported .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Successful and advantageous ozone treatment trials for the after clearing of disperse dyed polyester have been reported in the literature. These studies report the use of ozone at room temperature for shorter treatment times compared with conventional reduction clearing, with satisfactory colour difference values and wash fastness results for the ozone treatments .The potential benefits of ozone utilisation for the clearing of disperse dyed PET in terms of lower environmental pollution and water, energy, and time savings have been reported .…”
Section: Introductionmentioning
confidence: 91%
“…Other reductive agents include thiourea dioxide (TUDO), inorganic salts, reducing agents that do not require alkali, and liquid reducing agents . The oxidative clearing of PET with oxidative agents, either hydrogen peroxide or ozone, has also been reported in the literature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone was studied in treatment of wastewater and decolorization of textile wastewater by Poznyak et al (2007), Zhang et al (2007), Selcuk and Meric (2006), Perincek et al (2007), and Eren and Anis (2009). In the literature there is no study identified about ozone injection of circular conduits.…”
Section: Ozonementioning
confidence: 99%
“…The ozonation process has also shown its effectiveness for reduction clearing of polyester fibers (Eren 2007;Eren and Anis 2009). Its success to wash off unfixed reactive dyes cost-effectively from cotton fabrics, without compromising colorfastness properties has been recently reported both on laboratory and pilot scales (Shaikh et al 2010;Shaikh and Ahmad 2013).…”
Section: Introductionmentioning
confidence: 99%